Do CMT, SCC, and Bacteriological isolation overlap in subclinical mastitis cases of Anatolian buffaloes? - GONCAGÜL, Gülşen; GÜNAYDIN, Elçin; LİSUZZO, Anastasia; FİORE, Enrico; ÇOKAL, Yavuz; ZEYBEK, Melis (Etlik Veteriner Mikrobiyoloji Dergisi, 2023)
Abstract Subclinical mastitis is the most important and costly disease in the dairy sector. In this study, it was aimed to compare the results of bacteriological examination with those of California Mastitis Test (CMT) and Somatic Cell Count (SCC)in the milk samples collected from Anatolian buffaloes with no clinical signs of mastitis. For this purpose, 96 milk samples were collected from 24 Anatolian buffaloes of each quarter. All milk samples were examined for the presence of mastitic pathogens by bacteriology regardless of SCC values and CMT scores. A total of 103 isolates were recovered from the infected quarters. The first three frequently isolated mastitic pathogens were determined to be E. coli, S. agalactiae, and S. aureus with the rate of 31.07%, 22.33%, and 21.36%, respectively. According to the bacteriology results, threshold value for SCC was accepted as ≥78.000 cells/ml. The correlation value between CMT and SCC, CMT and bacteriology, and SCC and bacteriology was found as 0.737, 0.845 and 0.872, respectively, and the mean of inter-item correlation was determined 0.818. These results showed that the test results were highly correlated with each other. The results of the ROC analysis of the cut-of-value of the SCC test for this study chosen as 78.000 cells/ml supported the results obtained from the reliability analysis with sensitivity 85% and 1-specifity 100%. To sum up, a combination of CMT, SCC, and bacteriological investigation provides benefits in detecting mastitis early and avoiding misdiagnosis, allowing for timely action and treatment. Keywords: Anatolian Buffalo, CMT, SCC, bacteriology
Keywords: Veterinary Surgery; Anadolu süt mandası; CMT; SCC; bakteriyoloji; Veteriner Cerrahi; Anatolian Buffalo; CMT; SCC; bacteriology; 2. Zero hunger; 3. Good health